Optimizing the labyrinth geometric parameters and modelling a new twin seal configuration for improved sealing efficiency in gas turbines - Vijayaragavan, B.; Asok, S. P.; Marichelvam, M. K. (Frontiers in Mechanical Engineering, 2025)
Labyrinth seals are the non-contact seals used in turbo machinery to control the leakage of the secondary fluid flow. The main compressor supplies the compressed air required to generate hot gases in the combustion chamber. The secondary fluid is the part of the compressed air from the main compressor, which is used for cooling the inner components of turbomachinery. The non-contact nature of the seal results in an additional expense of compressed cooling air, which increases the power input to the main compressor. An improvement in the labyrinth’s sealing efficiency increases turbomachines’ fuel efficiency. The sealing characteristics of the labyrinth profile are highly influenced by the geometric parameters of the labyrinth seal. The geometric parameters of the straight-through labyrinth seal are optimized towards reduced leakage flow, and the optimized parameters are used to develop a new type of “Twin Labyrinth Seal.” The design variables considered in the optimization studies are tooth thickness, cavity width, and cavity depth of the labyrinth, while leakage mass flow rate is the variable to be minimized. Leakage characteristics for different configurations of the twin labyrinth seal are explored using numerical analysis. The standard k-epsilon two-equation viscous model simulates turbulence in the flow through the labyrinth path. The twin labyrinth configuration E with the least leakage is identified with an improved leakage control by 38% compared to the straight-through configuration of the tooth-on stator type. The results from the numerical analysis are validated with experiments. The significance of the effective clearance and divergence angle on the leakage characteristics of the twin labyrinth are discussed.